ACUTE GASTROENTERITIS IN CHILDREN-THERAPEUTIC PRINCIPLES - Victoria Hurduc; Valeriu Popescu; Dimitrie Dragomir; Doina Pleșca; Luiza Preda (Amaltea Medical Publishing House, 2008)
This report presents updated recommendations for the optimal management of acute gastroenteritis in childhood, according to fundamental therapeutical principles recommended by ESPGHAN ( European Society of Paediatric Gastroenterology, Hepatology and Nutrition). The authors underline the importance of the correct estimation of dehydration therapy considered as the "cornerstone" of therapeutical success. Finally the therapeutic and adverse effects of the main antidiarrhoeal drugs are presented, which played an adjuvant role in most cases. The authors emphasize the advantages of a newer generation drug-racecadotril, a selective and powerful intestinal antisecretory agent, considered a safe and efficient component of the management of acute diarrhoea in addition to oral rehydration therapy